HbA1c Control in Type 2 Diabetic Patients with Coronary Artery Disease - Mhlaba, Lona (University of the Witwatersrand, Johannesburg, 2023)
Background: Type 2 diabetes mellitus (T2DM) patients with coronary artery disease (CAD) have an increased risk of recurrent cardiovascular events. These patients require optimal glucose control to prevent the progression of atherosclerotic cardiovascular disease (ASCVD). Current guideline recommendations target an HbA1c ≤7% to mitigate this risk. This study evaluated the level of HbA1c control in T2DM patients with CAD. Methods: This retrospective study assessed consecutive patients who presented with CAD to the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) between April 2017 and December 2019. The study included T2DM patients on anti-diabetic medication with angiographically confirmed CAD. HbA1c control was assessed using the HbA1c level measured at the index presentation and during the most recent follow-up visit. Results: The study population comprised 262 T2DM patients with a mean age was 61.3 ±10.4 years. Among the T2DM patients, 188 (71.8%) were males. At index presentation, 110 (42.1%) T2DM patients presented with ST-segment elevation myocardial infarction, 69 (26.4%) had non-ST-segment elevation myocardial infarction, 43 (16.5%) had unstable angina, and 39 (14.9%) had stable angina. The baseline median systolic blood pressure was higher in patients with an HbA1c ≤7% [136 mmHg (Interquartile range (IQR): 117-151) vs 124 mmHg (IQR: 112-142), p= 0.0121], compared to those with an HbA1c level above 7%. Furthermore, T2DM with an HbA1c ≤7% also had a higher median diastolic blood pressure [85 mmHg (IQR: 75.5-97) vs 78 mmHg (IQR: 71-88), p=0.0205]. After a median follow-up of 16.5 months (IQR: 7-29), 28.7% of the study participants had an HbA1c ≤7%. On multivariable regression analysis, patients with ST-segment depression on the resting electrocardiogram and index presentation had optimal glycaemic control (Odds ratio: 0.27, CI: 0.12-0.59, p= 0.001). Conclusion: After a median follow-up duration of 16.5 months, only 28.7% of T2DM patients with CAD had optimal glycaemic control. This finding underscores the substantial unmet need for optimal diabetes control in this very high-risk group.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine (Internal Medicine), to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Diabetes mellitus; HbA1c; Coronary artery disease; Glucose control; Africa; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education